Neuropeptide Y directly reduced apoptosis of granulosa cells, and the expression of NPY and its receptors in PCOS subjects - Urata, Yoko; Salehi, Reza; Wyse, Brandon A.; Jahangiri, Sahar; Librach, Clifford L.; Tzeng, Chii-Ruey; Osuga, Yutaka; Tsang, Benjamin (Journal of ovarian research, 2023)
Background Most women with anovulatory infertility show polycystic ovarian syndrome (PCOS), and androgen excess is known as a key factor involved in pathogenicity of PCOS. However, the mechanism of follicular developmental arrest in PCOS is not completely understood. The reproductive function of Neuropeptide Y (NPY) in the ovary during folliculogenesis was previously reported; NPY function in apoptosis and proliferation of granulosa cells (GCs) is follicular-stage dependent. The objective of this study was to investigate the role of NPY in ovarian follicular development and the pathogenesis of PCOS. Methods To simulate the PCOS phenotype using a rat model, 21-day old Sprague Dawley rats were implanted with dihydrotestosterone (DHT) capsule (83 [micro]g/day) and euthanized after 28 days. mRNA and protein content of NPY and its receptors were assessed in GCs from DHT treated rats using RT-qPCR and Western blot, respectively. Proliferation and apoptosis of GCs was assessed using Ki67- and TUNEL assays. Finally, NPY levels were measured in human follicular fluid (FF) from matched PCOS and non-PCOS patients using ELISA. Results GCs from DHT treated rats (PCOS-GCs) contained significantly less NPY protein and Npy mRNA by 0.16- and 0.56-fold, respectively, and more NPY receptor type 2 and 5 protein by 2.21- and 3.17-fold, respectively, when compared to sham control. Addition of recombinant NPY to PCOS-GCs culture did not alter Ki67-positive but significantly decreased TUNEL-positive cells by 0.65-fold, but not to baseline levels. There was no significant difference in NPY levels in FF between PCOS and non-PCOS subjects. Conclusions These results indicate that DHT modulates expression of NPY and its receptors, NPY decreases DHT-induced GCs apoptosis. That alterations in NPY's function might be involved in follicular developmental failure of PCOS. Keywords: Neuropeptide Y, Neuropeptide, Apoptosis, Hyperandrogenism, Polycystic ovarian syndrome